On the Impact of Quotas and Decision Rules in Ultimatum Collective Bargaining - Veronika Grimm; Robert Feicht; Holger Rau; Gesine Stephan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We conduct multi-person one-shot ultimatum games that reflect important aspects of collective bargaining. In all treatments a proposer has to divide a pie among herself and six recipients that are divided into two groups of three. The proposer cannot discriminate among, but across group members. Acceptance decisions are taken by a committee of three representatives from one or both groups. In a 2x2 design we vary (i) representation in the decision committee (one vs. both groups) and (ii) the decision rule (unanimity vs. majority voting). We find that (i) representation of a group in the committee is crucial for receiving a significant share, (ii), proposals are more balanced if both groups have veto power (iii) acceptance rates are only high when the environment gives a clear idea of what an appropriate proposal is. Non–binding communication reduces rejection rates and proposer shares.
Keywords: C92; C78; C91; 330